2016
DOI: 10.1007/s00299-016-1957-3
|View full text |Cite
|
Sign up to set email alerts
|

Spermine modulates the expression of two probable polyamine transporter genes and determines growth responses to cadaverine in Arabidopsis

Abstract: Two genes, LAT1 and OCT1 , are likely to be involved in polyamine transport in Arabidopsis. Endogenous spermine levels modulate their expression and determine the sensitivity to cadaverine. Arabidopsis spermine (Spm) synthase (SPMS) gene-deficient mutant was previously shown to be rather resistant to the diamine cadaverine (Cad). Furthermore, a mutant deficient in polyamine oxidase 4 gene, accumulating about twofold more of Spm than wild type plants, showed increased sensitivity to Cad. It suggests that endoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Cadaverine treatment promoted putrescine and spermine accumulation while reducing spermidine content. On the other hand, spermine was also shown to modulate plant’s sensitivity to cadaverine, as discussed earlier in this review ( Sagor et al, 2016 ). Taken together, these initial studies are exciting because they begin to explore possible crosstalk between the cadaverine and putrescine-derived pathways in the modulation of root growth.…”
Section: Cadaverine Modulates Plant Developmentsupporting
confidence: 57%
See 2 more Smart Citations
“…Cadaverine treatment promoted putrescine and spermine accumulation while reducing spermidine content. On the other hand, spermine was also shown to modulate plant’s sensitivity to cadaverine, as discussed earlier in this review ( Sagor et al, 2016 ). Taken together, these initial studies are exciting because they begin to explore possible crosstalk between the cadaverine and putrescine-derived pathways in the modulation of root growth.…”
Section: Cadaverine Modulates Plant Developmentsupporting
confidence: 57%
“…Until recently, the well-characterized polyamine transporters in plants, including members of the L -Amino acid Transporter family (LAT proteins, also named Polyamine Uptake Transporters (PUTs)) and Organic Cation Transporters (OCTs), had been primarily investigated for function in the transport of putrescine-derived polyamines or other organic cations ( Mulangi et al, 2011 ; Fujita et al, 2012 ). OCT1, on the other hand, was suggested to function as a cadaverine efflux transporter because oct1 knockout plants are known to display increased sensitivity to cadaverine ( Strohm et al, 2015 ), and because spermine synthase over-expressing plants respond to cadaverine by increasing OCT1 expression, possibly to eliminate excessive polyamine from the cells ( Sagor et al, 2016 ).…”
Section: Is Environmental Cadaverine Taken Up By Plants?mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experimental studies renamed Arabidopsis LAT1 as Resistant to Methyl Viologen1 (RMV1) and Polyamine Uptake Transporter 3 (PUT3), and LAT4 as Paraquat Resistant1 (PAR1) and Paraquat-Resistant 2 (PQR2) (Dong et al 2016;Fujita et al 2012;Li et al 2013;Mulangi et al 2012). In planta studies suggested that Arabidopsis RMV1/LAT1/PUT3 mediates paraquat (a structural analog of polyamine) and cadaverine (a diamine derivative of lysine) import (Fujita et al 2012;Sagor et al 2016). Yeast complementation studies showed that this transporter also mediates polyamine and thiamine import (vitamin B1) (Martinis et al 2016;Mulangi et al 2012).…”
Section: R a F Tmentioning
confidence: 99%
“…Loss of PAR1/LAT4 function showed increased paraquat tolerance compared to WT suggesting that PAR1/LAT4 mediates paraquat transport (Dong et al 2016;Li et al 2013). Another member of this family, RMV1/LAT1 mediated increased polyamine uptake when over-expressed and increased paraquat tolerance when knocked out (Fujita et al 2012), showed increased cadaverine sensitivity when over-expressed (Sagor et al 2016) and mediated thiamine transport (Martinis et al 2016). In this report we have demonstrated that PAR1/LAT4 plays a role in leucine transport.…”
Section: Par1/lat4-family Transporters Interact With a Broad Range Ofmentioning
confidence: 99%